A Novel Chemical Route to Prepare La2Zr2O7 Pyrochlore. Issue 3 (9th November 2012) - Kong, Linggen; Karatchevtseva, Inna; Gregg, Daniel J.; Blackford, Mark G.; Holmes, Rohan; Triani, Gerry; Vanderah, T.
<x xml:space="preserve">Abstract</x> Lanthanum zirconate has been prepared via a new chemical synthesis method by combining sol–gel processing and complex precipitation. The synthesis was carried out in aqueous solution under ambient conditions. The synthesized powder possessed the pyrochlore superstructure upon calcination above 1200°C. A suite of characterization techniques, including FTIR, Raman, X‐ray and electron diffraction, TEM, SEM, and nitrogen sorption were employed to investigate the microstructural evolution and bulk properties. Dense ceramics (>90% relative density) were obtained after sintering at 1400°C, without need for additional processing (i.e., hot or cold isostatic pressing) or any milling steps. A mechanism has been proposed that elucidates molecular assembly of this chemical synthesis method.